1988
DOI: 10.1017/s0950268800067364
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of campylobacter excretors among Liberian children related to environmental conditions

Abstract: SUMMARYCampylobacter was the bacterial pathogen most prevalent in 859 children, aged 6-59 months, examined in a house-to-house diarrhoea survey in two Liberian communities. 44-9 % of the children from an urban slum and 284 % from a rural area were exeretors. Since the prevalence of diarrhoea was very high and consequently many convalescent carriers were found, it was not possible to evaluate the pathogenic role of campylobacter.The exeretor rate increased with age and was significantly correlated to the use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 37 publications
(36 reference statements)
2
12
0
Order By: Relevance
“…The high prevalence of dogs which are intestinal carriers, together with the wide distribution of C. jejuni and C. coli biotypes among stray dogs, as well as our findings in surface water 7 suggest that envivonmental conditions play an important role in this epidemiological picture. Similar findings have been observed in developing countries among children living in poor, crowded and contaminated urban slums 11 . This is probably, an epidemiological aspect that could also be found in relation to other animal populations.…”
supporting
confidence: 85%
“…The high prevalence of dogs which are intestinal carriers, together with the wide distribution of C. jejuni and C. coli biotypes among stray dogs, as well as our findings in surface water 7 suggest that envivonmental conditions play an important role in this epidemiological picture. Similar findings have been observed in developing countries among children living in poor, crowded and contaminated urban slums 11 . This is probably, an epidemiological aspect that could also be found in relation to other animal populations.…”
supporting
confidence: 85%
“…The high level of detection by the EIA or PCR methods is not surprising. Prior studies using less selective culture conditions have revealed a high burden of Campylobacter in infants in the developing world (18,19). Similarly, PCR-based detection of C. jejuni/C.…”
Section: Discussionmentioning
confidence: 99%
“…Among less rigorous studies, use of on-plot water was associated with lower incidence and prevalence of shigellosis among children (p<0.05) (Hollister et al, 1955;Rajasekaran et al, 1977;Stewart et al, 1955;Watt et al, 1953) and lower cholera incidence (p=0.02) (Wang et al, 1989). On-plot water access was not associated with prevalence of campylobacteriosis among children (Molbak et al, 1988) or household dysentery incidence (Wang et al, 1989). In two of the less rigorous studies not reporting a health benefit, children from households with on-plot water sources had significantly higher giardiasis and diarrhea prevalence than children from households using shared sources (p<0.001, p<0.05), but the statistical analyses were conducted by chisquared tests and did not account for factors such as sanitation, hygiene, water source type, and water quality (Ryder et al, 1985;Mason et al, 1986).…”
Section: Diarrheal Diseasesmentioning
confidence: 99%